(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
Owing to extensive hepatic first pass metabolism, Edaravone (EDV) shows low bioavailability (60 %) when administered orally, this leads to frequent administration of drug which may show toxicity. To overcome the above demerits of oral drug delivery of EDV, the present study is intended to prepare and evaluate EDV-loaded chitosan (CS) nanoparticles (EDV@CS-NPs) for the nose to brain delivery of EDV by ionic gelation technique. Chitosan, a biodegradable and mucoadhesive polymer, was selected for entrapment of EDV. The formulated, EDV@CS-NPs were characterized by UV-Visible spectroscopy, FT-IR spectroscopy, particle size analyser, zeta sizer, DSC, XRD, SEM, EDX, In vitro-Ex-vivo drug diffusion across goat nasal mucosa and Ex-vivo mucoadhesive study on goat nasal mucosa. The developed EDV@CS-NPs showed particle size of 200 ± 0.273 nm, polydispersity index (PDI) of 0.386, zeta potential -29 mV, an entrapment efficiency (EF) 97.52 ± 0.742%, and drug loading (DL) 22.72 ± 0.754%. The in vitro drug diffusion study displayed 91.80% of the drug release within 3 hours. The optimized batch (F2) showed the highest Ex-vivo drug diffusion up to 37.09 ± 0.24 % at the end of 3 hours. Further, DSC studies reveal absence of any incompatible interaction between EDV, and CS. SEM demonstrated a smooth morphology with an uneven shape. Elemental analysis reveals successful formulation of EDV@CS-NPs. Most importantly, better mucoadhesive strength of formulated nanoparticles was observed in Ex-vivo mucoadhesive study on goat nasal mucosa. Formulated EDV@CS-NPs may present a promising drug delivery system to treat many neurodegenerative illnesses like amyotrophic lateral sclerosis (ALS).